Sleep, Fatigue, Depression and Circadian Activity Rhythms in Women with Breast Cancer Before and After Treatment: A 1-year longitudinal study - Ancoli-Israel, Sonia (2014)
PURPOSE: Sleep disturbance, fatigue and depression are common complaints in patients with cancer, and often contribute to worse quality of life (QoL). Circadian activity rhythms (CARs) are often disrupted in cancer patients. These symptoms worsen during treatment, but less is known about their long-term trajectory. METHODS: Sixty-eight women with stage I-III breast cancer (BC) scheduled to receive ≥4 cycles of chemotherapy, and age-, ethnicity- and education-matched normal, cancer-free controls (NC) participated. Sleep was measured with actigraphy (nocturnal total sleep time [nocturnal TST] and daytime total nap time [NAPTIME]) and with the Pittsburgh Sleep Quality Index (PSQI); fatigue with the Multidimensional Fatigue Symptom Inventory-Short Form (MFSI-SF); depression with the Center of Epidemiological Studies-Depression (CES-D). CARs were derived from actigraphy. Several measures of QoL were administered. Data were collected at three time points: before (Baseline), end of cycle 4 (Cycle-4), and one year post-chemotherapy (1-Year). RESULTS: Compared to NC, BC had longer NAPTIME, worse sleep quality, more fatigue, more depressive symptoms, more disrupted CARs and worse QoL at Baseline (all p’s<0.05). At Cycle-4, BC showed worse sleep, increased fatigue, more depressive symptoms, and more disrupted CARs compared to their own Baseline levels and to NC (all p’s<0.05). By 1-year, BC’s fatigue, depressive symptoms and QoL returned to Baseline levels but were still worse than those of NC, while NAPTIME and CARs did not differ from NC’s. CONCLUSION: Additional research is needed to determine if beginning treatment of these symptoms before the start of chemotherapy will minimize symptom severity over time.